Contribution to the identification of medicinal plants used against COVID-19 in North-West Morocco - Laaribya, S.; Alaoui, A.; Azmi, R. (Regulatory Mechanisms in Biosystems, 2022)
The coronavirus disease 2019 (COVID-19) affects humans, who are now developing a milder form of the illness. In addition to the use of available drugs, the local populations in Morocco used medicinal plants during the pandemic. The current study aimed to document and to research the level of use of traditional medicine using plants in Morocco. Ethnobotanical surveys were conducted on the perceptions and level of use of plants through a case study in North-West Morocco. The methodology is based on targeted surveys, from April to September 2021, of households that have had cases if nfection with COVID-19. Five hundred surveys were randomly and systematically distributed in the study area to highlight the medicinal use of plants to treat COVID-19 and its consequences for health and well-being. The results showed the attachment of the populations to traditional medicine with the use of plants available in the study area (local forest area and herbalists). The 23 species used by the populations in question against COVD-19 belong to 12 families. The analysis shows the dominance of the Lamiaceae family with nine species, followed by Asteraceae with three species. The Lamiaceae family have proven marked performance in the fight against COVID-19. The results obtained offer orientations for the enhancement of the beneficial effects of traditional medicine and clinical trials remain to be carried out. The current results highlight that flora can be a source for the discovery of medicinal agents active against COVID-19.